2003
DOI: 10.1093/jac/dkg486
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane protein alterations and blaTEM-1 variants: their role in  -lactam resistance in Klebsiella pneumoniae

Abstract: Resistance to selected beta-lactams in two clinical isolates of K. pneumoniae was due to interplay between the expression of OMPs and TEM-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Indeed, a recent PubMed search for "resistant Klebsiella pneumoniae" yielded nearly 6,000 references. This is largely due to the rapid acquisition of extended-spectrum ␤-lactamases on plasmids (see reference 42), but many of the resistant isolates are also found to be lacking major porins (we cite here only early reports [6,[43][44][45][46]; in the review coauthored by one of us [4], we found that similar reports are so numerous in recent years that it was impossible to give exhaustive citations).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent PubMed search for "resistant Klebsiella pneumoniae" yielded nearly 6,000 references. This is largely due to the rapid acquisition of extended-spectrum ␤-lactamases on plasmids (see reference 42), but many of the resistant isolates are also found to be lacking major porins (we cite here only early reports [6,[43][44][45][46]; in the review coauthored by one of us [4], we found that similar reports are so numerous in recent years that it was impossible to give exhaustive citations).…”
Section: Discussionmentioning
confidence: 99%
“…In many parts of the world, K. pneumoniae is the most common species of the Enterobacteriaceae to contain one or more extended-spectrum ␤-lactamases that can confer resistance to expanded-spectrum cephalosporins (24,38,53). Several Ambler class C ␤-lactamases, many of them encoded on mobile genetic elements, have also been found in this species, further expanding ␤-lactam resistance to include cefoxitin and piperacillin-tazobactam (41).…”
Section: Discussionmentioning
confidence: 99%
“…OmpK37 is a small porin related to OmpN of Escherichia coli and is not normally expressed, while porins OmpK35 and OmpK36 play an important role in the penetration of antibiotics into the cell. Their loss can confer resistance to cephalosporins and carbapenems, particularly in strains containing Ambler group A, B, C, or D ␤-lactamases (5,8,19,30,38,40,44). Loss of OmpK35 plays a major role in antibiotic resistance, as illustrated in the K. pneumoniae CSUB10R deletion mutant (⌬ompK35 and ⌬ompK36) under complementation following transformation with a plasmid-encoded ompK35 gene (22).…”
mentioning
confidence: 99%
“…Porin loss is often caused by the insertion of an insertion sequence (IS) element (279). In the present century, reports on porin loss are so numerous that it is impossible to give an exhaustive list of the literature; we give only a few representative examples (280,281). We note, however, that clinical isolates resistant to carbapenems often lack porins (257,282,283).…”
Section: Klebsiella Pneumoniaementioning
confidence: 94%